Hubungan Antara Musik dan Sastra dalam Upacara Kahiya pada Masyarakat Mawasangka Kabupaten Buton Tengah Sulawesi Tenggara - Watulea, Ilham (TAMUMATRA, 2020)
Kahiya as one of the local wisdoms that is still maintained and run by the Mawasangka people’s. Although there have been many studies in the context of the kahiya rites that have been done, this research is categorized as research that has not been done much. This study aims to analyze the relationship between music and poetry as well as the meaningful relationship in the kahiya rites. In a cultural context, kahiya is not only a form of rites for Mawasangka people’s especially women, but also as a cultural experience. Poetry in the form of a metaphor delivered to participants kahiya and instrumental accompaniment presented in the implementation of this rites has a purpose as a means to achieve something that is intended and to give participants kahiya to an understanding for life in the future. This is intended so that participants can understand, and practice teaching, when they get married and live in their environment. In conclusion, that the use of metaphors seeks to illustrate the understanding of certain experiences or situations using other languages, and while the music is presented as an accompaniment and forms the atmosphere in the kahiya rites procession, with Islamic teachings as the basic. This study tends to be a literature review, but refers to the results of previous studies that still have relationships with different locations.